Green Consumption Behavior in School - Nindy Notrilauvia; Aldri Frinaldi (Science and Environmental Journal for Postgraduate, 2021)
Human activities affect the environmental. Humans know the importance of protecting the environment, but they are often negligent with the waste they consumed. Education is a very significant factor in influencing Green Consumption Behavior (GCB).PBLHS is the right stimulus in fostering GCB because the implementation of PBLHS includes learning about water conservation, energy conservation, and waste management that influence GCB.With the environmental knowledge from the PBLHS, a strong attitude towards environmental conservation will be generated.But as an Adiwiyata school that has succeeded in carrying out PBLHS, there are still an attitude that does not reflect GCB. This study aims to examine the effects of environmental knowledge, environmental attitudes and 3R behavior towards GCB, as well as to analyze the effectiveness of Adiwiyata schools in fostering the green consumption behavior of the school residents. The type of research is descriptive qualitative with quantitative support. The sampling method used is nonprobability sampling with purposive sampling technique.The data is processed and analyzed using SPSS25 version. The method of this analysis used multiple linear regression. The analysis results showed that simultaneously, environment knowledge, environment attitude, 3R behavior, has a significant effect on GCB. The research also showed that Adiwiyataschool is quite effective in growing the green consumption behavior, and the Green consumption behavior of the Adiwiyata school residents is higher than non-Adiwiyata schools.